2008
DOI: 10.1037/0735-7044.122.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Septal infusions of the hyperpolarization-activated cyclic nucleotide-gated channel (HCN-channel) blocker ZD7288 impair spontaneous alternation but not inhibitory avoidance.

Abstract: Blockade of septal hyperpolarization-activated cyclic nucleotide-gated channels (HCN) impairs hippocampal theta, an effect that would be expected to impair memory. To test this hypothesis, the present experiments determined whether septal infusions of the selective HCN channel blocker ZD7288 would impair performance on two memory tasks that involve the septo-hippocampal system: spontaneous alternation (SA) and continuous multiple inhibitory avoidance (CMIA). Fifteen minutes prior to assessing SA or CMIA, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
(125 reference statements)
3
9
0
Order By: Relevance
“…In contrast, we have observed in preliminary experiments that septal infusions of similar amounts of R3/I5 or R3(BD23-27)R/I5 in rats had no marked effect on emotional memory, assessed using an inhibitory avoidance test (see Ma et al 2005; S Ma and AL Gundlach, unpubl.). The possible specificity of septal RLN3 signaling on spatial memory is consistent with findings demonstrating a specific role of septal hyperpolarization-activated cyclic nucleotidegated channels in promoting hippocampal theta generation and spatial working memory, but no effect on emotional memory (Cisse et al 2008). Septohippocampal system, spatial memory, relaxin-3 www.learnmem.org…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, we have observed in preliminary experiments that septal infusions of similar amounts of R3/I5 or R3(BD23-27)R/I5 in rats had no marked effect on emotional memory, assessed using an inhibitory avoidance test (see Ma et al 2005; S Ma and AL Gundlach, unpubl.). The possible specificity of septal RLN3 signaling on spatial memory is consistent with findings demonstrating a specific role of septal hyperpolarization-activated cyclic nucleotidegated channels in promoting hippocampal theta generation and spatial working memory, but no effect on emotional memory (Cisse et al 2008). Septohippocampal system, spatial memory, relaxin-3 www.learnmem.org…”
Section: Discussionsupporting
confidence: 82%
“…The effect of RLN3/RXFP3 signaling in the MS on a ''thetadependent'' behavior was investigated in rats in the SAT, a behavioral test using a four-closed-arm plus-maze that has been used extensively to quantify spatial working memory in rodents Lalonde 2002;Cisse et al 2008). The average number of arm entries made by rats across all treatment groups was not significantly different, indicating that the infusions of agonist and antagonist into the MS did not affect locomotor ability or cause hyper-or hypoactivity (Supplemental Table 1).…”
Section: R3/i5 Infusion Into Ms Enhances Hippocampal Theta Activity Imentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have surprisingly revealed that activation of α2-noradrenergic receptors does not inhibit I h through the classical mechanism of adenylate cyclase inhibition by G α i but rather via the phospholipase C-protein kinase C (PLC, PKC) activated by G βγ , yet it remains unknown wheather this activation is through actions of PKC on the channel itself or through an intermediary (Carr et al, 2007). Finally, a recent report has shown that inhibition of I h in the region, a manipulation that impairs the hippocampal theta rhythm, significantly impaired performance on a test of working memory (spontaneous alternations) but not a test of emotional long-term memory (continuous multiple trial inhibitory avoidance) (Cisse et al, 2008). I h thus appears to play an important role in WM within multiple brain regions.…”
Section: 2 Ih In Learning and Memorymentioning
confidence: 99%
“…Both the involvement of HCN to and its altered expression in seizures depend on specific brain areas and underlying subunits/isoforms (Adams et al 2009). HCN channels are progressively activated by hyperpolarization, do not inactivate during at least seven seconds (Thon et al 2014), are sensitive to cocaine (Campanac and Hoffman 2013), and contribute to septohippocampal memory processing (Cisse et al 2008). …”
Section: Introductionmentioning
confidence: 99%